Relationship Between PTEN and Angiogenesis of Esophageal Squamous Cell Carcinoma and the Underlying Mechanism - Yang, Chenbo; Chen, Chao; Xiao, Qiankun; Wang, Xiaoqian; Shou, Yuwei; Tian, Xiangyu; Wang, Shuaiyuan; Li, Hui; Liang, Yinghao; Shu, Jiao; Chen, Kuisheng; Sun, Miaomiao (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) has high morbidity and mortality rates owing to its ability to infiltrate and metastasize. Microvessels formed in early-stage ESCC promote metastasis. Phosphatase and tensin homolog (PTEN) mediates macrophage polarization, but its effect and mechanism on early ESCC angiogenesis are unclear. To explore the molecular mechanism underlying early ESCC metastasis through blood vessels, we investigated the relationship between PTEN/phosphoinositide 3-kinase (PI3K)/p-AKT protein levels, number of infiltrated macrophages, and angiogenesis in ESCC and ESCC-adjacent normal esophageal mucosa tissues from 49 patients. Additionally, PTEN was overexpressed or silenced in the esophageal cancer cell line EC9706, and its supernatant served as conditioning medium for M1 tumor-associated macrophages (TAMs). The culture medium of macrophages served as conditioning medium for esophageal tumor-associated vascular endothelial cells (TECs) to study the biological behavior of PTEN-plasmid, PTEN-siRNA, and control TECs. We found that M1 TAM infiltration in ESCC tissues was low, whereas M2 TAM infiltration was high. Microvessel density was large, PTEN was down-regulated, and the PI3K/AKT pathway was activated in ESCC specimens. These parameters significantly related to the depth of tumor invasion, lymph node metastasis, and pathological staging of ESCC. Silencing of PTEN in EC9706 cells significantly activated the PI3K/AKT signaling pathway in macrophages, promoting M1-to-M2 TAM polarization and enhancing TECs’ ability to proliferate, migrate, invade, form tubes, and secrete vascular endothelial growth factor. We believe that PTEN silencing in esophageal cancer cells activates the PI3K/AKT signaling pathway in macrophages via the tumor microenvironment, induces M2 TAM polarization, and enhances the malignant behavior of TECs, thereby promoting ESCC angiogenesis. Our findings lay an empirical foundation for the development of novel diagnostic and therapeutic strategies for ESCC.